2014
DOI: 10.1177/1357633x14552369
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site videoconferencing for home-based education of older people with chronic conditions: the Telehealth Literacy Project

Abstract: We examined the acceptability of multi-site videoconferencing as a method of providing group education to older people in their homes. There were 9 groups comprising 52 participants (mean age 73 years) with an average of four chronic conditions. Tablet computers or PCs were installed in participant's homes and connected to the Internet by the National Broadband Network (high-speed broad band network) or by the 4G wireless network. A health literacy and self-management programme was delivered by videoconference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 23 publications
3
70
0
Order By: Relevance
“…A study focusing on videoconferencing for providing group education to older adults with chronic conditions found that telehealth services had the potential to improve literacy about chronic disease self‐management. Participants with little computer experience received support using the telehealth equipment . This may indicate that some participants in the current study with organised support could obtain eHealth literacy also at steps 2 and 3.…”
Section: Discussionmentioning
confidence: 89%
“…A study focusing on videoconferencing for providing group education to older adults with chronic conditions found that telehealth services had the potential to improve literacy about chronic disease self‐management. Participants with little computer experience received support using the telehealth equipment . This may indicate that some participants in the current study with organised support could obtain eHealth literacy also at steps 2 and 3.…”
Section: Discussionmentioning
confidence: 89%
“…It can also be an efficient mode of delivering group support to elderly people in rural areas. While developing interventions for older people using new technology is often considered difficult (Jang-Jaccard et al 2014), our study demonstrates that older people can be supported in using customised tablets and videoconferencing which provides realtime interactions and is inclusive of older people with limited or no prior use of computing (Banbury et al 2014a, Nancarrow et al 2014.…”
Section: Using Videoconference Groups For Social Supportmentioning
confidence: 64%
“…), our study demonstrates that older people can be supported in using customised tablets and videoconferencing which provides real‐time interactions and is inclusive of older people with limited or no prior use of computing (Banbury et al . , Nancarrow et al . ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to learning styles, another aspect to consider is the health literacy of clients to ensure there is adequate training and support for the recommended technology (Banbury et al, 2014). Many healthcare professionals provide written educational materials to clients, but they do not take into account the clients' reading level or health literacy (Banbury et al, 2014). The United States Department of Health and Human Services (2000) and Healthy People 2010 describe health literacy as the ability to comprehend basic health information required to make decisions regarding their healthcare.…”
Section: Teach Students To Assess Health Literacy and To Modify Instrmentioning
confidence: 99%